Stress Analysis of FGM Rotating Disk Subjected to Mechanical and Thermal Loads In Aircraft Gas Turbine Engine - Behrooz Shahriari; Mehrdad Safari (Mechanics of Advanced Composite Structures)
Pursuant to the high usage of rotating the disk in aircraft gas turbine engine, turbo pumps in oil and gas industries, steam and gas turbines in power plants, marine gas turbine and other industrial rotary machines designing and getting under the mechanical and thermal loading casued this design and analysis to be as a special significance. These disks are subjected to mechanical and thermal loads. In this article, four methods, variable material properties (VMP), Galerkin, Runge-Kutta with two different rules compute the amount of displacement, stress, and strain of a rotary disk, which has been applied from a functionally graded material (FGM). The problem in dissimilar states of loading and temperature dependence and independence of the properties has been resolved. Disk properties with the specified function of radius change. Mechanical loading conditions result from the centrifugal disk and blades mounted on it and the effects of shaft pressure and thermal stress caused by temperature difference in the shaft. The results acquired through every four methods are closed together and can be applied to analyse the problems of this type. Combining all loads, the most radial stresses and environmental stresses respectively obtained in the center of the inner and outer radius and inner radius of the disk. Through applying the results can get most optimal design of the (FGM) disk.